2018
DOI: 10.1515/cclm-2018-0824
|View full text |Cite
|
Sign up to set email alerts
|

Central adrenal insufficiency: open issues regarding diagnosis and glucocorticoid treatment

Abstract: Background Central adrenal insufficiency (CAI) is characterized by impaired adrenocorticotropin (ACTH) secretion because of a disease or injury to the hypothalamus or the pituitary, leading to a reduced cortisol production. CAI suspicion arises more frequently in patients with pituitary tumors, cranial irradiation/surgery/injury/infections, as well as after exogenous glucocorticoid withdrawal. Nevertheless, a late diagnosis is not uncommon because CAI may present with nonspecific signs or symptoms, as fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 86 publications
0
38
0
10
Order By: Relevance
“…The shift to MRHC was generally well tolerated except for three patients that preferred the previous treatment. The observation that patients with pAI were more frequently treated with MRHC than those with sAI both at baseline and at the end of the study is not completely unexpected since MRHC has been extensively studied only in pAI [33] while data in sAI are less conclusive. Mongioì et al have recently reported a less beneficial effect on metabolic profile in sAI patients treated with MRHC [34], although also in these patients was reported a maintained improvement in the clinical condition and subjective well-being.…”
Section: Discussionmentioning
confidence: 88%
“…The shift to MRHC was generally well tolerated except for three patients that preferred the previous treatment. The observation that patients with pAI were more frequently treated with MRHC than those with sAI both at baseline and at the end of the study is not completely unexpected since MRHC has been extensively studied only in pAI [33] while data in sAI are less conclusive. Mongioì et al have recently reported a less beneficial effect on metabolic profile in sAI patients treated with MRHC [34], although also in these patients was reported a maintained improvement in the clinical condition and subjective well-being.…”
Section: Discussionmentioning
confidence: 88%
“…As our multivariate logistic regression analysis indicated, postoperative adrenal insu ciency signi cantly affected the occurrence of PCNSI [20,21]. According to a previous study, much of the excess mortality in patients with adrenal insu ciency is attributable to infectious diseases [22].…”
Section: Discussionmentioning
confidence: 69%
“…[24] Central adrenal insufficiency was evaluated with basal serum cortisol or after a short Synacthen test when appropriate. [25] Diagnosis of other hormone deficiencies (central hypothyroidism or hypogonadism) was based on low or inappropriately normal pituitary hormone levels with lower than normal serum fT4 or gonadal steroid hormones.…”
Section: Methodsmentioning
confidence: 99%